2006
DOI: 10.2116/analsci.22.721
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Beryllium in Solid Samples by Flame Atomic Absorption Spectrometry after Preconcentration on Activated Carbon

Abstract: It is generally supposed that the preconcentration procedure is used for the determination of metal concentrations under the sensitivity of the measurement method. This study showed that preconcentration is also need for the beryllium (Be) concentration over the sensitivity of atomic absorption spectrometry. For this purpose, a simple and selective method for the determination of Be in solid samples is modified. The method is based on the preconcentration of the complexes of beryllium-acetylacetone plus morin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Yaman and Avci 50,51 pre-concentrated Be in the form of Beacetylacetone plus morin, oxine, PAN and PAR on activated carbon at different pH values. Recoveries of up to 85% were achieved following elution with aqua regia.…”
Section: Pre-concentrationmentioning
confidence: 99%
“…Yaman and Avci 50,51 pre-concentrated Be in the form of Beacetylacetone plus morin, oxine, PAN and PAR on activated carbon at different pH values. Recoveries of up to 85% were achieved following elution with aqua regia.…”
Section: Pre-concentrationmentioning
confidence: 99%
“…However, the most effective method for separation and enrichment of trace metals from aqueous solutions seems to be adsorption of heavy metals onto activated carbons because of their large surface area, high adsorption capacity, micro-pore character and high degree of surface reactivity (Dobrowolski, achieved simply by adjusting pH to the appropriate value or by application of a chelating agent (Camel, 2003). In the case of nickel and cobalt enrichment on activated carbon, this is done after chelating with: pyrocatechol violet (Narin et al, 2000), 8-hydroxyquinoline (Shiowatana et al, 2000), 4-(2 pyridylazo) resorcinol (Chakrapani et al, 1998), cupferron (Yaman and Gucer, 1998), 1,10-phenanthroline (Mikuła and Puzio, 2007), diethyldithiocarbamate (Kilicel and Gokalp, 2005), ammonium pyrrolidinedithiocarbamate (Soylak et al, 1996), dithioxamide (Ghaedi et al, 2007a), or N,N 0 -ethylenebis (ethane sulfonamide) (Karacan and Aslantas, 2008). The disadvantage of these procedures is that they require series of complexation steps (Daorattanachai et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Allen et al, (Allens et al, 1998) reported plasma and furnace atomic spectroscopies in which an atomic pressure microwave digestion procedure is described for the determination of copper, lead and nickel in edible oils. Another method proposed by Yaman et al, (Yaman et al, 1998), involved the determination of nickel in vegetable matrixes by AAS, after pre-concentration on activated carbon. Among the simpler atomic absorption spectroscopic methods requiring minimal manipulation and lowest probability of sample contamination, solubilizing and extraction of total trace metals from oil matrixes have also been used over the years (Flider et al, 1981;Persmers et al, 1971).…”
Section: Introductionmentioning
confidence: 99%